123 Physicians associates: a unique model at GOSH providing front line surgical care. (December 2018) - Patel, N; Kerr, S; Curry, J
Abstract : The medical workforce in the modern NHS is evolving constantly to meet the needs of an ever more complex patient population. Specialist Neonatal and Paediatric Surgery (SNAPS) at GOSH represents the pinnacle of surgical complexity for which a high level of skill and knowledge is required for a stable and consistent work force. The previous model of a large pool of Junior Doctors to recruit from is no longer tenable so SNAPS has looked at Physician Associate's (PA) to provide this care. A PA is a professional that works within the medical/surgical team adding to the diverse skill mix to help underpin healthcare delivery. They work within the team to assess, examine and manage care alongside doctors. But what makes PAs unique is their ability to provide continuous care. They are a vital link to all other healthcare personnel providing continuity and ensuring seamless, high quality care. They provide a familiar face in a daunting hospital environment and help support the families. Currently, within SNAPS, there are two PAs embedded into the team. They are involved in ward rounds, clerking emergency and elective patients for theatre and developing clinical surgical skills through regular observed assessment. They currently work weekdays facilitating continuous care for inpatients and their families. The role is unique to the organisation but experience across many other major hospitals is increasing year on year. Thanks to a generous grant from the hospital charity there will be 3 newly qualified PA's joining the surgical teams, thus, by the end of 2018, there will be more PA's involved in surgical specialities at GOSH than any other paediatric surgical unit in the UK. They are a vital key to the continued provision of a world-class surgical service and GOSH remains at the cutting edge of healthcare innovation.